(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article reveals the life and scientific activity of the thinker Muhammad FazlBalkhi, who lived in the Middle Ages in Urgut District of Samarkand, his human qualities, the importance of religious and mystical heritage today. Historical data about the scientist named “KhojaiOmon” are summarized.